Highly Efficient Preparation of Cyclic Dinucleotides via Engineering of Dinucleotide Cyclases in Escherichia coli - Lv, Yun; Sun, Qichao; Wang, Xiaodan; Lu, Yi; Li, Yaoyao; Yuan, Huiqing; Zhu, Jing; Zhu, Deyu (Frontiers in Microbiology, 2019)
Cyclic dinucleotides (CDNs) are widely used secondary signaling molecules in bacterial and mammalian cells. The family of CDNs includes c-di-GMP, c-di-AMP and two distinct versions of hybrid cGAMPs. Studies related to these CDNs require large doses that are expensive to generate by currently methods. Here we report what are to our knowledge the first feasible microbial-based method to prepare these CDNs including c-di-GMP, 3’3’-cGAMP and 2’3’-cGAMP. The method mainly includes two parts: producing high yield of CDNs by engineering the overexpression of the proper dinucleotide cyclases (DNCs) and other related proteins in E. coli, and purifying the bacteria produced CDNs by a unified and simple process involving STING affinity column, macroporous adsorption resin and C18 reverse-phase liquid chromatography. After purification, we obtained the diammonium salts of c-di-GMP, 3’3’-cGAMP and 2’3’-cGAMP with weight purity of > 99%, > 96%, > 99% and in yields of > 68, > 26, and > 82 milligrams per liter of culture, respectively. This technology platform enables the production of CDNs from cheaper material, provides a sustainable source of CDNs for scientific investigation, and can be easily further developed for industry to prepare CDNs on a large scale.